(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
In the world, in the pedagogical theory and practice, there exist several models of educational work in the pre-school, elementary school and high school education. The appearance of such models has initiated a different approach to the educational aspect of the children and pupils, which is based on the influential scientific achievements regarding the development of the child in this period. The Democratic Political pluralism opened up new possibilities towards instigating the so-called “educational pluralism ”9, which leads towards a spectrum of educational alternative possibilities. A part of this concept concerns the ideas of Rudolf Steiner, described through the educational philosophy with its characteristics as being original. The Waldorf pedagogy represents one part of the rare models whose pedagogical foundations, ideas and tendencies are implemented in quite a specific didactic-methodic constellation. In such a context, special emphasis in this text is put on the issue of rhythm as an elementary strategy in the planning and programming of the educational process.